Research on optimal production decision for 'company + farmer' based on farmland leasing model. (2018) - Yu, Jianjun; Huang, Xiaoyong; Lyu, Kunye
To study the problem of the optimal production decision of risk-neutral company and risk-averse farmer under the 'company + farmer' rental model, this paper is based on the traditional newsboy model from the perspective of supply chain coordination. By introducing a leasing model, the optimal production decision of supply chain is analysed in case of considering expected rents. For the case of considering the expected rent, the risk-averse farmer's production decision-making problem is discussed by introducing conditional value-at-risk (CVaR) and the conclusion is drawn that when facing the lower labour costs of agricultural products, the farmer can effectively avoid risks by using rental model under the 'company + peasant household'.